Prp19 Is an Independent Prognostic Marker and Promotes Neuroblastoma Metastasis by Regulating the Hippo-YAP Signaling Pathway - Cai, Yuanxia; Chen, Kai; Cheng, Cheng; Xu, Yonghu; Cheng, Qianqian; Xu, Guofeng; Wu, Yeming; Wu, Zhixiang (Frontiers in Oncology, 2020)
Pre-mRNA processing factor 19 (Prp19) was previously reported to be involved in tumor progression. However, Prp19 expression and its functions remain elusive in neuroblastoma. Here, we aim to identify the functions and mechanisms of Prp19 in neuroblastoma. Neuroblastic tumor tissue microarrays and two independent validation data sets indicate that Prp19 is associated with high-risk markers and bone marrow metastasis and serves as a prognostic marker for worse clinical outcomes with neuroblastoma. Gain- and loss-of-expression assays reveal that Prp19 promotes invasion, migration, and epithelial–mesenchymal transition (EMT) of neuroblastoma cells in vitro. Bioinformatics analysis of RNA-seq data shows that the expressions of YAP and its downstream genes are significantly inhibited after downregulation of Prp19. Prp19 and YAP expression in metastatic lymph nodes is higher than in situ neuroblastoma tissue. Further experiments show that Prp19 regulates YAP expression and consequently affects cell invasion, migration, and EMT in neuroblastoma by pre-mRNA splicing of YAP. In conclusion, our findings provide the first evidence that Prp19 is a potential therapeutic target and prognostic biomarker for patients with neuroblastoma.